Нейроендокринна регуляція функціонування серця людини-донора - Салютін, Р. В.; Паляниця, С. С.; Давидова, Т. І.; Комарова, Л. С.; Соколов, М. Ф. (Clinical Endocrinology and Endocrine Surgery, 2013)
The lecture presents data on the effect of neuroendocrine processes on the function of the heart muscle of a human donor and the means to maintain and optimize the conditions for maintaining the quality and function of the heart on the background of progressive disorders of homeostasis.